Design and analysis of two layers RLC network of rectangular topology by wave concept iterative process method. (8th September 2020) - Ammar, Noemen; Vincent, Didier
Abstract: The paper presents a theoretical study of a rectangular electrical network built on two layers. First, the auxiliary source notion is introduced for characterizing the potential difference over each electrical element, then the mathematical formalism of the Wave Concept Iterative Process method is developed and adopted to the studied circuit. The used method is based on the concept of the incident and reflected waves which are defined from the current and voltage at each branch of the circuit. Two relations connecting the waves are established into two definition domains: a spectral‐domain using the Kirchhoff laws and the auxiliary source connections and, another spatial defining the boundary conditions and the circuit design. Hence a two equations system is obtained and it is resolved by an iterative process, the transition between the two domains is ensured by the fast Fourier transform and its inverse. Moreover, the equivalent impedance between the feeding source and the nodes of the bottom layer has been calculated. Among the numerical simulation methods, this method has demonstrated its performances for analyzing various designs of the networks including RL, RC and RLC circuits excited by a lumped voltage source. The effect of the circuit parameters on the electrical currents and equivalent impedance has been studied.